A comparison of three infant skinfold reference standards: Tanner–Whitehouse, Cambridge Infant Growth Study, and WHO Child Growth Standards. Issue 4 (13th February 2014) - Miller, Elizabeth M.
Abstract As researchers increasingly focus on early infancy as a critical period of development, there is a greater need for methodological tools that can address all aspects of infant growth. Infant skinfold measures, in particular, are measurements in need of reliable reference standards that encompass all ages of infants and provide an accurate assessment of the relative fatness of a population. This report evaluates three published reference standards for infant skinfold measurements: Tanner–Whitehouse, Cambridge Infant Growth Study, and the World Health Organization (WHO) Child Growth Standards. To assess these standards, triceps skinfolds from a population of rural Kenyan infants (n = 250) and triceps skinfolds and subscapular skinfolds from infants in the National Health and Nutrition Examination Survey 1999–2002 (NHANES; n = 1197) were calculated as z‐scores from the lambda‐mu‐sigma curves provided by each reference population. The Tanner–Whitehouse standards represented both the Kenyan and US populations as lean, while the Cambridge standards represented both populations as overfat. The distribution of z‐scores based on the WHO standards fell in the middle, but excluded infants from both populations who were below the age of 3 months. Based on these results, the WHO reference standard is the best skinfold reference standard for infants over the age of 3 months. For populations with infants of all ages, the Tanner–Whitehouse standards are recommended, despite representing both study populations as underfat. Ideally, the WHO will extend their reference standard to include infants between the ages of 0 and 3 months.